Antibiotic Resistance: A Macromolecule Reversing Antibiotic Resistance Phenotype and Repurposing Drugs as Potent Antibiotics (Adv. Sci. 17/2020). Issue 17 (9th September 2020) - Ding, Xin; Yang, Chuan; Moreira, Wilfried; Yuan, Peiyan; Periaswamy, Balamurugan; de Sessions, Paola Florez; Zhao, Huimin; Tan, Jeremy; Lee, Ashlynn; Ong, Kai Xun; Park, Nathaniel; Liang, Zhen Chang; et al.
Abstract : In article number 2001374, James L. Hedrick, Yi Yan Yang, and co‐workers show that guanidiniumfunctionalized polycarbonates reverse the antibiotic resistance phenotype, and improve antibiotic potency via intracellular protein precipitation, gene binding and subsequent reactive oxygen species generation. Importantly, the polymer allows for the effective repositioning of rifampicin and auranofin meant for Gram‐positive bacteria and arthritis, respectively, to be highly effective against multidrugresistant Gram‐negative bacteria both in vitro and in vivo.